IDENTIFIKASI POLIFENOL PADA KULTUR IN VITRO KALUS Camellia sinensis UNTUK BAHAN MINUMAN FUNGSIONAL (Jurnal Teknologi Pangan, 2013)
Polyfenol  included  secondary  bioactive  metabolite  had  a  function  to  reduce  degenerative syndrome. Polyfenol contained in tea act as bioactive syntesis from hydroksil part and could be act as functional drinking and  control human organ as biological metabolism. Problem in  gain polyfenol productfrom tea plantation / camellia sinensis L  for intance : depent on season, need  a large area for  cultivication,  and  low  contain  for  productivity.For  thesepurpose  there  were  main  idea  to ncrease polyfenol  productivity  by  mean  of  in  vitro  culture  technique.  These  technique  could  reduce  all problem  above.  The  main  purpose  of  these  research  were  to  find  production  technique  by  mean callus  culture.    Method  to  gain  the  purose  were  :  (1)  callus  induction  by  cultify  part  of tea  leaves  in many variance  grown culture , (2)  Sub culture callus  using same culture  media  as callus   induction (3)  Morphologycal  check  for  callus  (4)  Kualitative  analisys  callus  polyfenol.Result  of these  research were  callus with hand time retention (tR) on High Performace Liquid Chromatography for 14 minutes with a same time of standart poyfenol.  Polyfenol had potential to support  the retention of functional beverage.Key words : Polyphenols,  in vitro culture of  callus , Camellia sinensis